"Cycles of Change": Slaying the Badger, the Tour de France and Contemporary Documentary Film. (December 2017) - Howley, Colin Paul
From its origins in 1903 as a parochial national cycle race, the Tour de France is today undeniably among the greatest annual sporting spectacles in the world. Since 1954 it has systematically extended its appeal beyond France's national borders, regularly staging a grand départ from other European cities. The Tour de France also attracts an estimated 12 million spectators lining the route over the race's 3-week duration every year, is watched by a reputed 1.5 billion global television audience across more than 188 countries and, therefore, is implicitly involved in a complex production of transnational discourses about sport. This article analyzes the 2014 ESPN documentary Slaying the Badger and proposes a reading which situates the representation of Greg LeMond (the first and, to date, only officially recognized American to win the Tour de France) and his turbulent rivalry with teammate and mentor French cyclist Bernard Hinault within wider social contexts. Focusing on the discourse of "Americanization, " the article also critically examines the meanings of socioeconomic forces that began to transform not only the international composition of the peloton but also the cultural significance of the Tour de France from the 1980s onward.